Community-Based Nutrition Intervention by PT Borneo Indo Bara: A CSR Case Study - Zainal Arifin; Hafizianor Hafizianor (Indonesian Journal for Social Responsibility, 2026)
Stunting continues to be a major public health concern in Indonesia, especially in rural and impoverished areas.  According to the 2024 Indonesian Nutritional Status Survey, the frequency of stunting has dropped to 22.9% in South Kalimantan and 19.8% nationwide. To address this persistent issue, PT Borneo Indo Bara (PT BIB) started the CERIA (Cegah Stunting Raih Impian Anak) Cooking Class as a component of its CSR initiative to promote nutritional enhancement in the community. In this study, the CERIA Cooking Class in Teluk Kepayang District, Tanah Bumbu Regency, South Kalimantan, is implemented and its effects on the community are examined. Targeting five ring-1 areas that encircle the working region of PT BIB, the initiative involves 30 participants per district, including local nutritionists, PKK members, and community health workers. The program emphasizes maternal and child nutrition using locally sourced ingredients, in keeping with the national B2SA (Diverse, Nutritious, Balanced, and Safe) food movement. It includes culinary demonstrations and nutrition education created in partnership with Chef Agus Sasirangan and public health experts. In-depth interviews with local government representatives, program organizers, and community members who participated were used to collect qualitative data.  The initiative successfully encouraged the use of local food resources, increased knowledge of stunting prevention, and developed multi-sectoral collaboration, according to the results. The study emphasizes how community-driven and culturally appropriate CSR programs can support national nutrition goals.